The Great Escarpment of southern Africa: a new frontier for biodiversity exploration - Clark, V.; Barker, N.; Mucina, Ladislav (Springer, 2011)
The biodiversity of the 5,000 km-long Great Escarpment of southern Africa is currently poorly known, despite hosting half of the subcontinent’s centres of plant endemism and to have a rich endemic vertebrate fauna, particularly in the north-west and east. A country-based overview of endemism, data deficiencies and conservation challenges is provided, with Angola being the country in most need of Escarpment research and conservation. Given that the Escarpment provides most of the subcontinent’s fresh water, protection and restoration of Escarpment habitat providing such ecological services is urgently required. Key research needs are exhaustive biodiversity surveys, systematic studies to test refugia and migration hypotheses, and the effects of modern climate change. Such research results can then be consolidated into effective conservation planning and co-ordinated international efforts to protect the rich biodiversity of the Escarpment and the ecological services it provides.